Pengaruh Pelaksanaan Pelvic Rocking Dengan Birthing Ball Terhadap Pengurangan Nyeri Pinggang Persalinan Kala I Diwilayah Puskesmas Mamboro Kota Palu - Niluh Nita (Viva Medika, 2020)
ABSTRACT Pain is a feeling of distress or pain, which acts as a warning that the network is being damaged. Every maternal, experiencing pain that makes mothers uncomfortable and in pain so that researchers want to do or apply pelvic rocking with birthing ball to relieve back pain stage labor I. This study aimed to investigate the effect of pelvic rocking with birthing ball towards the reduction of back pain first time delivery at Mamboro Health Center, Palu City. The method used is the Pre-experiment with the Pretest-posttest One Group. The population of this study was all mothers who came to the Mamboro Health Center. The sampling technique of this study is accidental sampling. The data analysis used was univariate analysis and bivariate analysis with the Wilcoxon Rant Test. Results of thetest Wilcoxon values obtained significancy sebesar0,033, statistically shows that there are significant pelvic rocking the birthing ball against lumbar pain reduction stage labor pain Tier I. Pre test was mostly at severe pain by 16 respondents (53.3% ) and moderate pain as many as 14 respondents (46.7%). The level of pain in the Post test was that some mothers were in moderate pain 21 respondents (70%), severe pain as many as 9 respondents (30%). The conclusion of this research that there is the effect of the implementation of pelvic rocking with birthing ball towards the reduction of back pain first stage of labor in the health center Mamboro Palu, due to the implementation of pelvic rocking with birthing ball is respondents feel more relaxed so that the psychological state does not focus the pain she felt. The results of this study are expected to be applied in health facilities such as hospitals, maternity clinics and health centers. Keywords: Pain intensity and pelvic rocking with birthing ball